Redescription of the rare species Podospongia loveni (Porifera) from the Cantabrian Sea - Cristobo, J.; Ríos, P.; Sánchez, F.; Anadón, N. (Continental Shelf Research, 2009)
Podospongia [du Bocage, B., 1869. Eponges siliceuses nouvelles du Portugal et de l’Iˆle Saint-Iago (Archipel de Cap-Vert). Jornal de Sciencias mathematicas, physicas e naturais 2, 159–162], which at present includes only ?ve species, is a rare genus generally found in deeper waters down to 600 m depth from Natal coast in South Africa, to New Caledonia, the Central and North Atlantic and the Mediterranean Sea. Species of this genus are characterised by a choanosomal skeleton composed of tracts of megascleres radiating from a centrum and stipitate body. Microscleres are spinorhabds and aciculospinorhabds packed in a vertical arrangement in the ectosome and scattered throughout choanosome. As a result of two oceanographic projects (Ecomarg, date; Cocace, date) on the continental shelf of the Cantabrian Sea, ten stipitate sponge specimens were collected and assigned to Podospongia loveni [du Bocage, B., 1869. Eponges siliceuses nouvelles du Portugal et de l’Iˆle Saint-Iago (Archipel de Cap-Vert). Jornal de Sciencias mathematicas, physicas e naturais 2, 159–162]. Since the holotype was destroyed [Kelly, M., Samaai, T., 2002. Family Podospongiidae de Laubenfels, 1936. In: Hooper, J.N.A., Soest, RW.M., (Eds.), Systema Porifera: A Guide to the Classi?cation of Sponges, New York, pp. 694–702] and with the existence of several specimens from a close region, we hereby redescribe this species. scanning electron microscopy pictures of the spicules and skeletal architecture of P. loveni are for the ?rst time provided.